The Tale of the Shipwrecked Sailor and the Rite of Passage - Abbas, Eltayeb.
The Tale of the Shipwrecked Sailor is subjected to a new sociological evaluation in light of the theories concerning rites of passage. Included therein are an analysis of its elaborate structure and how it relates to the rite of passage.